ANALISIS LITERASI EKONOMI DAN PERILAKU KONSUMEN (Survey pada Guru SMA di Kota Bandung) - Budiwati, Neti (2014)
Analysis of Economic Literacy and Consumers' Behavior (Survey at High School's Teachers in Bandung), Neti Budiwati (1102723), under the guidance of: Prof.Dr.H.Disman, MS., Prof.Dr.H.Agus Rahayu, MP.,and Dr.Kusnendi, MS. This research is based on the signs of the irrational consumers' behavior in the community, and the low level of economic literacy in the community. The purposes of this study were to: (1) describe the effect of interaction in regular trips, socialization, shopping routines, and interaction from period of stay, economic considerations and non-economic considerations on consumption behavior of high school teacher; (2) describe the effect of interaction in regular trips, shopping routines, socialization and interaction from period of stay on economic literacy of high school economics teachers. The population in this study consists of high school teachers in Bandung, both from public and private high schools. Sampling was conducted using proportional random sampling technique, with sample of 355 teachers. The research method used in this study is explanatory survey research. The data were collected using questionnaires and a test of economic literacy, while the data analysis technique used was Structural Equation Modeling (SEM). Based on the result of data analysis, the research findings obtained were as follows: (1) Teachers' learning experience from routine activities such as regular trips, socialization, and period of stay is a form of hidden knowledge (Tacit Knowledge) which will eventually, through the process of externalization with the help of the creativity of the teachers,change into explicit knowledge; in addition, the level of economic literacy of high school teachers is still in low conditions, and the consumption behavior of high school teachers tends to be irrational; (2) Consumption behavior is directly influenced by the factors of regular trips, socialization, shopping routines, and period of stay. Regular trips, socialization, shopping routines, and period of stay also indirectly influence consumption behavior through economic literacy. Besides, consumption behavior is also influenced by economic and non-economic considerations. The variable of learning experiences with the biggest influence is routine shopping, followed by socialization, while the smallest is period of stay; and (3) Economic literacy is empirically influenced by the factors of regular trips, socialization, shopping routines, period of stay, economic considerations, and non-economic considerations. The factor of routine shopping is a dominant factor in influencing economic literacy. It can be concluded that the more meaningful the learning experience is, the better the level of economic literacy is, which eventually results in a more rational consumption behavior among high school teachers. ---------- Keywords : experiential learning, economic literacy, consumer behavior,tacit knowledge